STUDI PERENCANAAN NORMALISASI SUNGAI BABAKAN KABUPATEN BREBES - Okky Hendra (Engineering : Jurnal Bidang Teknik, 2021)
Abstract: In early 2020, from January to February, 6 floods were recorded, the worst was when the embankment overflow occurred in the villages of Kemurang Wetan, Kemurang Kulon and Pejagan. The cause of flooding in the Babakan River is high rainfall intensity and is not supported by an adequate river cross-sectional capacity. From the results of the planned rainfall analysis, it was found that the average rainfall in the Babakan River Basin was 81.63 mm. The research locations are located in three points which include Kubangwungu Village with a plan length of 750 meters, Sutamaja Village with a plan length of 300 and Kemurang Wetan Village with a plan length of 1000 meters. From the observation location research of flood discharge was recorded 91.56 m3/ sec and average daily discharge is 1:45 m3 / sec. At the existing conditions, the cross section of the river is able to accommodate a discharge of 91.56 m3 / s based on a simulation of the flow profile calculation with the help of Software HEC-RAS 5.0.7. Based on the calculation of the cross-sectional dimensions, it is found that the ideal cross-sectional detail is 30 meters wide, 5.2 high and 4 meters wide with Q plan, namely Q50 721.33 m3 / s with the assumption of a discharge of 510,353 m3 / s with the shape of the cross section according to conditions in the field, either using slope 1 : 2 and 1: 1.